2012
DOI: 10.1177/0883073812446310
|View full text |Cite
|
Sign up to set email alerts
|

Height Assessments in Children With Neurofibromatosis Type 1

Abstract: Previous studies have suggested that children with neurofibromatosis type 1 (NF1) are shorter than their unaffected counterparts. Unfortunately, these reports did not consider other contributing factors that might also influence short stature. The purpose of the current study was to characterize the genetic influence of NF1 on the growth of children. Height data was measured and recorded for 170 patients, while parental measurements were obtained for 61 patients to calculate sex-corrected mid-parental target h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
2
18
1
1
Order By: Relevance
“…The only exception was the presence of tumors (several types, see Table S2; excluding those present in the major NF1 criteria), with frequencies similar in index patients fulfilling and not fulfilling the NF1 criteria. Most minor features were found (in index patients fulfilling the NF1 criteria) in a frequency comparable with that described in literature (30,(35)(36)(37)(38). Speaking problems were observed in 16.7%, which is much lower than the 65% previously reported (39).…”
Section: Discussionsupporting
confidence: 79%
“…The only exception was the presence of tumors (several types, see Table S2; excluding those present in the major NF1 criteria), with frequencies similar in index patients fulfilling and not fulfilling the NF1 criteria. Most minor features were found (in index patients fulfilling the NF1 criteria) in a frequency comparable with that described in literature (30,(35)(36)(37)(38). Speaking problems were observed in 16.7%, which is much lower than the 65% previously reported (39).…”
Section: Discussionsupporting
confidence: 79%
“…Short stature, characterised by a height of more than two standard deviations below the predicted mean, is evident in 8–13% of children with NF1 (Szudek et al 2000; Sbidian et al. 2012; Soucy et al 2013) whilst a body height below the third percentile has been observed in 15% of children with NF1 (Clementi et al 1999). …”
Section: Genotype–phenotype Relationships In Patients With Nf1 Microdmentioning
confidence: 99%
“…Prognosis is generally good, although most children will be below-average height 4 8. Up to 70% of children affected with NF1 will have some learning difficulties, and most will have IQs in the low-average range 9.…”
Section: Answers To the Questions On Pagementioning
confidence: 99%